Sistemas de Formación Musical y Fomento de Valores en Colombia, Chile y Venezuela, Visto a Través del Documental - López C., Ana María (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
From three documentaries that narrate the history of prominent figures and groups, and it show the different faces of the programs of musical formation for young people and children in three countries of Latin America, we enter the knowledge of these systems or nets, of the conflicts and successes raised for his protagonist, stretching as backdrop the normative and historical frame of his existence, and his meaning as strategy of social incorporation and as method created to attack the disorder in the Latin-American countries. We approach the topic in three paragraphs: in relation with the documentary narratives and the way like they construct the histories; the comparison of the paths of these initiatives in every country and the evolution of his relations with the State; and the critical reading from the social semiosis like an interpretation of the initiative
Keywords: Documentaries; Systems of Musical Formation; Audio-visual Analysis; Latin-American